Sputtered ruthenium oxide coatings for neural stimulation and recording electrodes. Issue 5 (17th September 2020) - Chakraborty, Bitan; Joshi‐Imre, Alexandra; Maeng, Jimin; Cogan, Stuart F.
Abstract: We have investigated the deposition and electrochemical properties of sputtered ruthenium oxide coatings for neural stimulation and recording electrodes. A combination of oxygen and water vapor was used as a reactive gas mixture during DC magnetron sputtering from a ruthenium metal target. The sputtering plasma was monitored by optical emission spectroscopy to determine the reactive species present and confirm the control of plasma chemistry by reactive gas flow rates into the deposition chamber. The effect of the O2 :H2 O gas ratio on the microstructure and electrochemical properties of the ruthenium oxide were studied in detail. We employed a combination of surface characterization techniques, including scanning electron microscopy, x‐ray diffraction, and x‐ray photoelectron spectroscopy, to understand the relationship between plasma chemistry and the microstructure of the films produced under different gas flow conditions. Electrochemical characterization included cyclic voltammetry, electrochemical impedance spectroscopy, and voltage transient measurements, performed on planar ruthenium oxide electrodes with a geometric surface area of 1960 μm 2 . At an O2 :H2 O gas flow rate ratio of 1:3, a cathodal charge‐storage capacity per unit film thickness of 228.7 mC cm −2 μm −1 (median, Q1 = 134.5, Q3 = 236.6, n = 15) and a charge‐injection capacity (0.6 V anodal interpulse bias) of 7.4 mC cm −2 (median, Q1 = 6.9, Q3 = 8.3, n = 15) were obtained in phosphate buffered saline. The charge‐injection capacity of ruthenium oxide sputtered with water vapor in the reactive plasma is comparable with sputtered iridium oxide (SIROF) and higher than reported values for porous TiN, a commonly employed high‐surface area stimulation electrode coating.